Asset encumbrance in euro area banks: Analysing trends, drivers and prediction properties for individual bank crises - Pierre Berthonnaud; Enrico Cesati; Maria Ludovica Drudi; Kirsten Jager; Heinrich Kick; Marcello Lanciani; Ludwig Schneider; Claudia Schwarz; Vasileios Siakoulis; Robert Vroege (European Central Bank (ECB), 2021)
Asset encumbrance is a central concept in the context of banks' liquidity crises, as it is associated with their capacity to obtain secured funding. This occasional paper summarises the work carried out by the task force on asset encumbrance, bringing together analyses by the ECB and those national competent authorities working on the topic. First, we describe how asset encumbrance has evolved in euro area banks, focusing on country and business model aggregates. Second, we conduct an econometric analysis of the driving factors of banks' asset encumbrance, highlighting the relevance of credit risk, the availability of high quality collateral suitable for encumbrance, capital and sovereign funding conditions. Third, we turn our focus to the asset encumbrance dynamics of banks that have experienced a crisis. The outcome of this event study analysis indicates that asset encumbrance increases in the lead-up to a crisis, partly to offset early deposit outflows. Building on these findings, we show that asset encumbrance indicators carry predictive information for bank-specific crises as part of a multivariate early warning model.
Keywords: G21; G01; G28; C23; C49; 330; asset encumbrance; liquidity; bank funding; collateral; bank crisis; earlywarning model; panel econometrics